Deterrence works for criminals - Menusch Khadjavi (Kiel Institute for the World Economy (IfW), 2014)
Criminal law and economics rests on the expectation that deterrence incentives can be employed to reduce crime. Prison survey evidence however suggests that a majority of criminals are biased and may not react to deterrence incentives. This study employs an extra-laboratory experiment in a German prison to test the effectiveness of deterrence. Subjects either face potential punishment when stealing, or they can steal without deterrence. We confirm Gary Becker's deterrence hypothesis that deterrence works for criminals.
Keywords: C72; C91; C93; K42; 330; Crime; Stealing; Deterrence; Prison; Extra-laboratory experiment; Artefactual field experiment